The impact of travel blog and vlog on travel decision making among university students - Mohd Zamri, Nur Fatihah; Saad, Mazni (2019)
The young travellers’ segment is a developing market for today’s travel and hospitality industry. They are attracted in the advancement of technology, specifically the students. All the information, especially about travel can be obtained through online websites and applications. The travel decision making among the young generations also can easily be altered by using online sources. The presence of varieties of online sources regarding travel destinations has been more practical to search for the travel information especially travels blog and vlog. Online sources can simply affect decision making when it comes to travelling. However, with the varieties of online sources, it is difficult to identify if the information provided can be trusted or not. The decision making to travel can be changed in a minute and can be influenced by many factors. Therefore, this research is focusing on the travel blog and vlog as an online source that may influence the students’ travel decision making. It aims to study the aspects and trustworthiness of travel blogs and vlog that can affect their travel decision-making process. Hence, this research will be significantly helpful for marketers in developing marketing strategies in order to provide a better tourism experience and attract more tourists to the destination.